PENGARUH PERMAINAN KARDUS BEKAS TERHADAP KEMAMPUAN MATEMATIKA PERMULAAN PADA ANAK USIA 5-6 TAHUN DI TK SYAKHSHIYATUL UMMAH KECAMATAN SIAK HULU KABUPATEN KAMPAR - Chairilsyah, Daviq; Puspitasari, Enda; ', Helvanita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to determine the influence of used cardboard game against beginning math skills in children aged 5-6 years in kindergarten Syakhshiatul Ummah Siak Hulu District of Kampar. This type of research is experimental design with one group pretest posttest design. Population and sample in this study were 20 children aged 5-6 years in kindergarten Syakhshiatul Ummah Siak Hulu District of Kampar. Collection techniques namely direct observation of children's activities. Data were analyzed using t-test formula and method of statistical analysis with SPSS for windows release.16. The hypothesis of this study was the influence of used cardboard game against beginning math skills in children aged 5-6 years in kindergarten Syakhshiatul Ummah Siak Hulu District of Kampar. It can be seen from the analysis of data obtained t value amounted to 13.703, while t table with level sig (5 %) and (df = n - 1 = 20-1 = 19) t table amounted to 2,093. Because t is greater than t table or 13.703 > 2.093, it means that the influence of old cardboard games against beginning math skills in children aged 5-6 years in kindergarten Syakhshiatul Ummah Siak Hulu District of Kampar. Determinant coefficient generated is equal to r2 = 0,562. This means that the influences of used cardboard game against math skills in children beginning kindergarten Syakhshiatul Ummah by 56,2%. And can researchers conclude that the presence of cardboard used to influences the game math skills in children beginning kindergarten Syakhshiatul Ummah Siak Hulu District of Kampar.The keywords: Used Cardboard Game , Math Ability Beginning